Hyperbaric Oxygen Ameliorates Bleomycin-Induced Pulmonary Fibrosis in Mice - Yuan, Yuan; Li, Yali; Qiao, Guoqiang; Zhou, Yilu; Xu, Zijian; Hill, Charlotte; Jiang, Zhenglin; Wang, Yihua (Frontiers in Molecular Biosciences, 2021)
The prevalence of pulmonary fibrosis is increasing with an ageing population and its burden is likely to increase following COVID-19, with large financial and medical implications. As approved therapies in pulmonary fibrosis only slow disease progression there is a significant unmet medical need. Hyperbaric oxygen (HBO) is the inhaling of pure oxygen, under the pressure of greater than one atmosphere absolute and it has been reported to improve pulmonary function in patients with pulmonary fibrosis. Our recent study suggested that repetitive HBO exposure may affect biological processes in mice lungs such as response to wounding and extracellular matrix. To extend these findings, a bleomycin-induced pulmonary fibrosis mouse model was used to evaluate the effect of repetitive HBO exposure on pulmonary fibrosis. Building on our previous findings, we provide evidence that HBO exposure attenuates bleomycin-induced pulmonary fibrosis in mice. In vitro, HBO exposure could reverse, at least partially, transforming growth factor (TGF)-β-induced fibroblast activation, and this effect may be mediated by down-regulating TGF-β-induced expression of hypoxia inducible factor (HIF)-1α. These findings support HBO as a potentially life-changing therapy for patients with pulmonary fibrosis, although further research is needed to fully evaluate this.